Pengembangan E-Modul Interaktif Berbasis Matematika Realistik Di Kelas VIII SMP Swasta Palapa Telagah - Sovarina Yasarifa Pohan; Prihatin Ningsih Sagala (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to obtain a constructivism-based e-module that is valid, practical, and effective, so that it can assist students in understanding the material for a two-variable linear equation system. The research instruments used were lesson plans, material validation sheets and e-module media, learning outcomes tests, and student and teacher response questionnaire sheets. After all instruments, lesson plans, and e-modules were declared valid by the validator, then readability tests and field trials were carried out. The results showed that: (1) the developed E-Module had met the validity values, namely (3.37 and 3.25) with a very feasible category; (2) The developed E-Module has met the practical value (79.75% and 90.5%) with very practical category; (3) The developed E-Module meets the effective criteria with the completeness of student learning outcomes that meet the criteria, namely 85% of students have obtained a score of 75 and the achievement of each indicator/learning objective is more than 65% of the total students.